Assessing Worry About Affording Healthcare in a General Population Sample - Jones, Salene M. W.; Du, Yuxian; Panattoni, Laura; Henrikson, Nora B. (Frontiers in Psychology, 2019)
This study adapted a measure on worry about affording healthcare. The financial costs of healthcare are increasingly being shifted to patients. Financial burden from healthcare costs can be material (such as bankruptcy) or psychological. Psychological distress can be either worry about affording future care or distress due to material consequences and, despite evidence from clinical psychology that differentiates these types of emotional symptoms, this distinction has largely been ignored for financial burden in healthcare. We adapted a worry about affording healthcare scale for use in the general population (n=398) to facilitate comparisons between disease groups and across countries. Participants completed a survey through an online platform. The worry about affording healthcare measure showed good reliability and validity through associations with quality of life and measures of other types of financial burden. Worry about affording healthcare was also associated with cost-related non-adherence to medical care. Future research on patient quality of life should consider worry about affording healthcare.